Fatores de risco associados ao déficit neurológico em pessoas vítimas de acidente vascular cerebral isquêmico - Melo, Tailane Tavares de (2022)
Objective: To identify the risk factors associated with neurological deficit in people who victims of ischemic stroke. Methods: This is a retrospective quantitative descriptive study carried out in a hospital in the interior of Minas Gerais- Brazil. Data were collected from 52 medical records, using an instrument containing sociodemographic and clinical variables and treatment time windows. To assess neurological deficit, the National Institutes of Health Stroke Scale was used. The Shapiro-Wilk, Pearson Chi- square, T Student and McNemar testes were used for statistical analysis. The significance level was 0,05. Results: At hospital admission there was a prevalence of moderate neurological deficit, and at hospital discharge, mild neurological deficit. Neurological deficit values at hospital admission and discharge werw respectively 13,10 (±7,2) and 7,58 (±8,3), p = (0,000). The hospital stay was 7,78 days for individuals with mild/moderate neurological deficit and 11,67 days for severe neurological deficit (p=0,044). The needle door window time was 38 minutes for patients with mild/moderate neurological deficit and 55,3 minutes for severe neurological deficit (p=0,025). Conclusion: The influence of the neurological condition on the length of stay and the importance of prompt care by the team are highlighted.